MAKNA DAN PENGGUNAAN VERBA ‘MEMBANTU’ DALAM BAHASA JEPANG SEHARI-HARI: TINJAUAN SEMANTIK - I Wayan Wahyu Cipta Widiastika (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2021)
Japanese is a foreign language that has many variations of the lexicon. One of them is the lexicon variation in verbs. This study discusses the meaning and use of verb 'help' in everyday Japanese conversation. The data is in the form of sentences used by native Japanese speakers. Data collection was carried out through interviews and note taking techniques. The data were analyzed using the contextual meaning theory approach of Pateda, (2010 : 116). The result shows that there are eight variations of the verb 'help' in Japanese namely: tetsudau, tasukeru, osewa ni naru, sukuu, kyuujo suru, enjo suru, kifu suru, and ouen suru. From the analysis, the verb